Disseminated Peripheral Mycotic Aneurysms and Septic Embolizations Related to an Infected Stent Deployed for Restenosis of Surgically Repaired Supravalvular Aortic Stenosis - ŞAYLAN ÇEVİK, BERNA; AKALIN, FİGEN; AK, KORAY; ARSAN, SİNAN (SAGE PUBLICATIONS INC, 2016)
Percutaneous treatment of supravalvular aortic stenosis (SVAS) by means of balloon dilation and stent deployment has been rarely reported in the literature. In this report, we present the case of a patient with mycotic aneurysms, disseminated peripheral and cerebral septic embolizations, and infected vegetations associated with a stent that had previously been deployed to treat restenosis of surgically corrected SVAS in the infancy.
Keywords: supravalvular aortic stenosis; stent; infection; vegetations; ENDOCARDITIS